The Effect of Perceived Spiritual Leadership on Organizational Agility: A Field Study - Fettahlıoğlu, Ömer Okan; Döngül, Esra Sipahi; Hamid, Nur (SCAD Independent, 2025)
The current scenario compels businesses to adopt an agile structure to navigate unprecedented changes and to help employees adapt effectively. This study was conducted to support the hypothesis that spiritual leaders can guide employees in adapting to changes and enhancing organizational agility. Spiritual leadership can improve organizational agility by increasing employees’ trust and commitment, making it easier for them to adjust to change. Data were collected from 405 employees in both top- and bottom-level positions within the manufacturing industry in the Malatya and Kayseri provinces of Turkey. This quantitative research model was developed and tested using correlation and regression modeling techniques. The findings revealed a significant relationship and interaction between spiritual leadership and organizational agility (r = 303; and r = 504, p < 0.05)] (R 2: 028; p: 001. Business agility is achieved through adaptation to change, which necessitates that employees also adapt effectively to these changes.